Studying Socialization of the Individual during Adolescence - Sottiyeva Gozal Khasan qizi, Usmanaliyeva Sitora Ikromjon qizi, Ernazarova Sevinch Paxriddin qizi, Inomjonova Nozimakhon Bakhromjon qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article discusses the personal opinions of scholars regarding the socialization of individuals during adolescence, their life views, the psychological states of socialization during adolescence, and the factors influencing it.